The Effect of Invetation and Exports on Labor Absorption through Economic Growth in Indonesia - Rana Ameliya Rosa; Shalsa Aulia; Ade Nabilla Rabiullikha; Safuridar (International Journal of Business and Applied Economics, 2023)
This study aims to analyze the effect of investment and exports on employment through direct economic growth, then analyze the level of influence of labor absorption on the rate of economic growth directly, analyze the effect of investment on employment through economic growth and analyze exports on employment through economic growth in Indonesia. This study uses secondary data in the form of time series data, 2012-2021, namely investment data, exports, labor absorption and economic growth which are tested using path analysis techniques. The results showed that investment had a positive and significant effect on employment, while exports had a negative and insignificant effect on employment. Investment and exports have a positive and insignificant effect on economic growth. Labor absorption has a positive and insignificant effect on economic growth.